2010
DOI: 10.1007/s12565-010-0088-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variants of lateral meniscus of the knee: a cadaveric study in South Indian human fetuses

Abstract: In the present study, the objectives were to study the morphology of the lateral menisci (LMs) in human fetuses from a South Indian population and to verify the developmental etiology of the discoid lateral meniscus (DLM). The study included 106 fetal knee joints which were fixed in 10% formalin. After dissecting the joints, the morphological variants of the shapes of the LMs were macroscopically noted and classified as discoid and nondiscoid. The nondiscoids were subdivided into C-shaped and crescentic. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 22 publications
4
20
0
Order By: Relevance
“…Structural incompatibility between the femur and tibia may be the reason for many clinical problems, particularly MM injury. In adults, the shape, size and thickness of the LM are different to those of the MM ( 9 , 10 ). At the same time, it has been reported that the LM of the tibia in the adult surface footprint of the MM is larger than the area covered by the tibial surface.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…Structural incompatibility between the femur and tibia may be the reason for many clinical problems, particularly MM injury. In adults, the shape, size and thickness of the LM are different to those of the MM ( 9 , 10 ). At the same time, it has been reported that the LM of the tibia in the adult surface footprint of the MM is larger than the area covered by the tibial surface.…”
mentioning
confidence: 92%
“…The most common developmental anomaly is discoid meniscus ( 4 , 7 ). A number of researchers have reported a relation between meniscal injuries and discoid meniscus ( 4 , 8 , 9 ). During the foetal period, discoid meniscus is more commonly observed in the lateral meniscus (LM) ( 9 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations